Fear of Missing Out (FOMO) and Social Pressure in Generation Z’s Decisions to Marry in The Village of Astanajapura - Khofifah; Farida Nurfalah (Indonesian Journal Publisher, 2026)
Marriage is a significant life stage shaped by social norms, particularly in rural communities. Among Generation Z, social pressure and Fear of Missing Out (FOMO) can influence perceptions and decisions about marriage. This study aims to identify the forms of social pressure and FOMO experienced by Generation Z in Astanajapura Village, explore the factors contributing to FOMO, and describe their subjective experiences in responding to marriage-related expectations. Using a qualitative phenomenological approach, data were collected through in-depth interviews with five unmarried Generation Z participants. The data were analyzed using thematic analysis to identify recurring themes and emotional experiences. The findings reveal that FOMO is reflected in feelings of being left behind when peers marry first, a strong desire to marry immediately, and frequent social comparisons. These feelings are influenced by pressures from family, relatives, neighbors, and peers, as well as prevailing social norms regarding marriage. Despite experiencing anxiety due to social pressure and FOMO, participants considered mental, emotional, and financial readiness as the primary factors in deciding to marry rather than external expectations